Stan badań nad obrządkiem pogrzebowym ludności fazy łódzkiej - Borkowska, Grażyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1992)
The criteria of distinguishing the Łódź phase as the transitional stage from the culture of Trzciniec to Lusatian culture have not been clearly specified so far. Crematory rites of funeral having in common both Trzciniec and Lusatian features are adopted as the distinguishing mark. Known burials of Łódź phase can be attributed to two chronological groups of older and younger type. Graves of older type refer to flat crematory graves of the culture of Trzciniec. Characteristic features of theirs are: rectangular shape of the burial cave, stone constructions, the phenomenon of common burial and ceramics broken intentionally. Younger graves of Łódź phase are characterized by small burial caves or the presence of cinerary urns, by strong burning of bones and more varying inventory stock. These features and the continuity of cemeteries allow to relate closely the discussed cultural unit to the Lusatian culture. The analysis of the burial service certifies the definition of Łódź phase as the chronological phenomenon, middle between Trzciniec and Lusatian culture and it also confirms the significance of this stage, transitional both in burial rites and in other fields of life.